Lapatinib in combination with capecitabine versus continued use of trastuzumab in breast cancer patients with trastuzumab-resistance: a retrospective study of a Chinese population - Fan Yang (BMC Cancer, 2020)
Abstract Background The efficacy and safety of lapatinib plus capecitabine (LC or LX) versus trastuzumab plus chemotherapy in patients with HER-positive metastatic breast cancer who are resistant to trastuzumab is unknown. Methods We retrospectively analyzed data from breast cancer patients who began treatment with regimens of lapatinib plus capecitabine (LC or LX) or trastuzumab beyond progression (TBP) at eight hospitals between May 2010 and October 2017. Results Among 554 patients who had developed resistance to trastuzumab, the median PFS (progression free survival) was 6.77 months in the LX group compared with 5.6 months in the TBP group (hazard ratio 0.804; 95% CI, 0.67 to 0.96; P = 0.019). The central nervous system progression rate during treatment was 5.9% in the LX group and 12.5% in the TBP group (P = 0.018). Conclusion The combination of lapatinib and capecitabine showed a prolonged PFS relative to TBP in patients who had progressed on trastuzumab.